2011
DOI: 10.2149/tmh.2010-18
|View full text |Cite
|
Sign up to set email alerts
|

The Global Programme to Eliminate Lymphatic Filariasis: History and achievements with special reference to annual single-dose treatment with diethylcarbamazine in Samoa and Fiji

Abstract: Diethylcarbamazine (DEC), first introduced in 1947, was shown to have strong efficacy and safety for treatment of human lymphatic filariasis, which is caused mostly by a species Wuchereria bancrofti. Many studies to optimize the dosage and treatment schedule of DEC followed, and, based on the results, control programs with various regimens were implemented in different endemic areas/countries. By the mid 1970s, with endorsement by the WHO Expert Committee on Filariasis (3rd report, 1974), the standard DEC regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Reiter [20] reported that the oviposition behavior in the field might vary significantly both between species and within a species, albeit in different regions. Such differences are apparently related to environmental heterogeneity and the impact that human activities have on these mosquitoes [5,7,37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Reiter [20] reported that the oviposition behavior in the field might vary significantly both between species and within a species, albeit in different regions. Such differences are apparently related to environmental heterogeneity and the impact that human activities have on these mosquitoes [5,7,37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…However, in order to reach the goal of elimination by the year 2020, numerous challenges must be overcome. Elimination of LF requires annual MDA with high coverage and compliance for at least 5 years in order to interrupt transmission through the lifespan of adult worms [3], [4], [5], a difficult undertaking in light of logistical and financial constraints. Perhaps most importantly, thresholds for transmission cessation are currently unknown and are site-specific.…”
Section: Introductionmentioning
confidence: 99%
“…At this level the worms become infective and can transmit the disease. It takes about 10-14 days to develop from L1 to L3 [8]. When the infective mosquitoes bite the human, the worms move to human body.…”
Section: Introductionmentioning
confidence: 99%
“…WHO has determined that one of the drugs used is Diethylcarbamazine (DEC). Drug mass administration was conducted once every year for 4-6 years [8]. This treatment can kill microfilaria and partially kill adult worms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation